How many calories do nurses burn at work? A real-time study of nurses' energy expenditure. (November 2019) - Allan, Julia; Sadko, Klaudia; Bell, Cheryl; Johnston, Derek
Background: Nurses have high rates of overweight and obesity, and physical inactivity is one key determinant of weight gain. Aims: The present study aims to quantify nurses' energy expenditure over a standard 12-hour shift to establish whether activity levels at work are too low to maintain a healthy body weight. Methods: Ward-based nurses ( n  = 96, 90 female, mean age = 36 years, mean experience = 10 years, mean body mass index = 26.6) wore heart rate and physical activity monitors for the duration of one full working shift. Heart rate and activity data were used in combination with demographic information to estimate each nurse's energy expenditure over 12 hours. Results: On average, nurses burned 2.12 kcals per minute while at work, equating to 1521 kcals/6364 kJ ( SD  = 403 kcals/1686 kJ) per 12-hour shift. Energy expenditure over 12 hours varied markedly between nurses (from 812 kcals/3397 kJ to 3005 kcals/12, 573 kJ) but was sufficient in 72% of participants (assuming minimal resting levels of energy expenditure for the 12 hours not at work) to burn off a daily calorie intake of 2000 kcals. Conclusions: Three-quarters of nurses expend more energy on working days than is required to maintain a healthy body weight if dietary intake does not exceed recommended levels.